Peripheral Blood-Based Biopsy for Breast Cancer Risk Prediction and Early Detection - Nassar, Farah J.; Chamandi, Ghada; Tfaily, Mohamad Ali; Zgheib, Nathalie Khoueiry; Nasr, Rihab (Frontiers in Medicine, 2020)
Among women, breast cancer (BC) is not only the most common cancer worldwide but also the leading cause of cancer death. Only 5 to 10% of breast cancer cases are attributed to inherited mutations (BRCA1, BRCA2, and other breast cancer susceptibility genes). Breast cancer incidence has been rising particularly in young women who are not eligible for mammography, and it has been acting as a burden especially in developing countries that lack screening and awareness programs. For this reason, research has shifted to use noninvasive liquid biopsies especially blood-based biomarkers with potential value for breast cancer risk prediction and early detection. This mini review will tackle the different blood-based biomarkers focusing mainly on circulating miRNA, circulating proteins, cell-free nucleic acids, methylation patterns and exosomes. It also introduces the potential opportunities for the clinical use of these blood-based biomarkers for breast cancer risk prediction.